3D Flower‐Like Zinc Cobaltite for Electrocatalytic Reduction of Nitrate to Ammonia under Ambient Conditions. Issue 4 (27th January 2022) - Huang, Pingping; Fan, Tingting; Ma, Xintao; Zhang, Jiguang; Zhang, Yanping; Chen, Zhou; Yi, Xiaodong
Abstract: Nitrate (NO3 − ) as a common pollutant of groundwater causes drinking water safety problems and seriously endangers people's health. Electrochemical reduction of nitrate to ammonia under ambient condition is a green and significant route to reduce the concentration of NO3 − and produce ammonia (NH3 ), known as a complement to the Haber–Bosch reaction. Currently, noble‐metal electrocatalysts are often used in electrochemical reduction of NO3 −, but high cost and scarcity limited their application. Herein, three‐dimensional (3D) flower‐like zinc cobaltite (ZnCo2 O4 ) electrocatalyst was developed to convert nitrate into ammonia at room temperature. The NH3 yield rate could reach up to around 2100 μg mg −1 h −1 at a potential of −0.6 V vs. reversible hydrogen electrode (RHE), which was around 2.0 times higher than that of pristine Co3 O4 . In addition, the NH3 faradaic efficiency of ZnCo2 O4 electrocatalyst could reach around 95.4 % at potential of −0.4 V vs. RHE with good structural and morphological stability, which surpassed most reported non‐noble metal‐based electrocatalysts. Further studies concluded that the improved activity of electrocatalytic NO3 − reduction was ascribed to the existence of abundant active sites and the charge transfer from Co atoms to Zn atoms after Zn doping. Importantly, this work opens a new path for the development of Co‐based materials as electrocatalysts for reducing nitrate to ammonia. Abstract : Lowering barriers : Bimetallic ZnCo2 O4 catalyst can promote nitrate electroreduction at room temperature. The electron‐deficient Co active site can lower the energy barriers for the formation of *NO2 intermediate and suppress the hydrogen evolution reaction, thus enhancing the selectivity and yield rate of electrochemical NO3 − reduction to ammonia.